Tradisi Ngeropok dalam Perayaan Panjang Mulud di Kampung Gowok, Desa Sukajaya, Kec. Curug, Kota Serang, Banten (Studi Living Hadis) - Muhammad Fadli Hanif (PT. Saha Kreasi Indonesia, 2025)
This study examines the tradition of Ngeropok in the Panjang Mulud celebration in Kampung Gowok, Sukajaya Village, Curug District, Serang City, Banten, through the Living Hadith approach. The Panjang Mulud tradition is an annual ritual of the Banten community in commemorating the birth of the Prophet Muhammad SAW, which includes the activity of Ngeropok, namely the collection and carrying of Panjang Mulud containing food donations and egg decorations to the mosque. This study aims to describe the implementation of the Ngeropok tradition, analyze its symbolic meaning, and trace the transformation of Islamic values in local cultural practices. The method used is qualitative with an ethnographic approach, through participatory observation, in-depth interviews, and document studies. The results of the study show that the Ngeropok tradition is not only a medium for religious expression and gratitude, but also serves as a means of strengthening social solidarity and preserving culture. From the perspective of Living Hadith, this tradition represents the dynamics of the application of Islamic teachings that are alive and developing in the context of Banten society, while also reflecting the dialectic between religious authority, art, and local culture.